2014
DOI: 10.1007/s40618-014-0149-7
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the mysteries of the genetics of osteoporosis

Abstract: A future challenge will be to conduct fine mapping and functional analysis of the loci implicated in osteoporosis in order to identify the causal genetic variants and examine the mechanisms by which they influence bone cell function and bone mass. Ultimately this may lead to the identification of biomarkers for susceptibility to osteoporosis and fractures or new therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 76 publications
0
11
0
2
Order By: Relevance
“…Many advances have been made in defining the genetic determinants of BMD and fractures through large-scale GWAS, genome sequencing studies and linkage studies in rare bone diseases 32. For example, linkage studies have shown that loss-of-function and gain-of-function variants in LRP5 cause early onset osteoporosis33 and high bone mass,34 respectively, whereas loss of function mutations affecting SOST and LRP4 have been identified as causes of high bone mass and osteosclerosis 35 36.…”
Section: Discussionmentioning
confidence: 99%
“…Many advances have been made in defining the genetic determinants of BMD and fractures through large-scale GWAS, genome sequencing studies and linkage studies in rare bone diseases 32. For example, linkage studies have shown that loss-of-function and gain-of-function variants in LRP5 cause early onset osteoporosis33 and high bone mass,34 respectively, whereas loss of function mutations affecting SOST and LRP4 have been identified as causes of high bone mass and osteosclerosis 35 36.…”
Section: Discussionmentioning
confidence: 99%
“…Упродовж останніх років акцентується увага на значенні вітаміну D як імунного модулятора. Вітамін D проявляє свій ефект шляхом зв'язування з рецептором вітаміну D (VDR) і активації VDR-чутливих генів [3].…”
Section: вступunclassified
“…Excised skeletal elements such as individual femurs may also be analyzed. The majority of GWAS for loci controlling bone mass in humans have been based on these DXA measurements of BMD (911), and usually the focus is on either the lumbar spine or proximal femur (hip). In mice it is common to collect data for whole body BMD, as well as regions of interest encompassing several vertebrae or the entire femur.…”
Section: Genetic Loci Mapped For Bone Mineral Density In Micementioning
confidence: 99%
“…As a result, BMD is the most studied phenotype in bone from a forward genetics point of view. Indeed, in humans both common and rare genetic variants for this phenotype have been identified by GWAS, yet as is often the case with this type of study, the amount of variance collectively explained remains small (911). While these GWAS-identified loci have provided interesting and novel insights into the regulation of bone mass, BMD as a phenotype is an inadequate surrogate for bone strength or resistance to fracture, as we know from clinical studies that BMD is an imperfect predictor of fracture (12).…”
Section: Introductionmentioning
confidence: 99%